1977
DOI: 10.1177/107118137702100106
|View full text |Cite
|
Sign up to set email alerts
|

More Information or More Data?: Some Experimental Findings

Abstract: This paper reviews work which has investigated the relationship between the amount of information available to a decision maker and the quality of the resulting decision.Consideration is also given to research into the strategies employed by decision makers to cope with information overload. Some recent empirical results are presented which indicate that one must carefully distinguish between the amount of information and the amount of data given to the decision maker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Present strategies employed by decision makers to cope with IO. Also concerns on this concerns on information quality, it did not need lead to good decisions and that summarizing the information into a smaller set data could be useful [194], [195].…”
Section: ) Concerns On Io and Information Problemsmentioning
confidence: 99%
“…Present strategies employed by decision makers to cope with IO. Also concerns on this concerns on information quality, it did not need lead to good decisions and that summarizing the information into a smaller set data could be useful [194], [195].…”
Section: ) Concerns On Io and Information Problemsmentioning
confidence: 99%
“…Warnings can be mentally filtered out because of the presence of too much information, although it remains to be investigated how much is too much. Studies have demonstrated that too much information does degrade task performance (deTurk, 1995;Dorris, Connolly, Sadosky, & Burroughs, 1977). In a recent review on warning literature, Frantz and his colleagues suggest that there might be some potential negative consequences associated with providing large numbers of warnings (Frantz, Rhosdes, Young, & Schiller, 1999).…”
Section: Human Response To False Alarmsmentioning
confidence: 99%